Dynamics and mechanisms of volatile organic compound exchanges in a winter wheat field. (15th January 2020) - Bachy, A.; Aubinet, M.; Amelynck, C.; Schoon, N.; Bodson, B.; Delaplace, P.; De Ligne, A.; Digrado, A.; du Jardin, P.; Fauconnier, M.-L.; Mozaffar, A.; Müller, J.-F.; et al.
Abstract: The understanding of biogenic volatile organic compound (BVOC) exchanges has become a key scientific issue because of their high reactivity and their impact in the atmosphere. However, so far, few studies have focused on BVOCs exchanged by agricultural species, and in particular by winter wheat, despite this species being the leading worldwide crop in terms of harvested area. This study for the first time investigated BVOC exchanges from winter wheat during most developmental stages of the plant. Fluxes were measured in Belgium at the ecosystem-scale using the disjunct eddy covariance by mass scanning technique, and a proton-transfer-reaction mass spectrometer for BVOC ambient mixing ratio measurements. As is usually observed for crops and grasses, the winter wheat field emitted mainly methanol, although bi-directional exchanges were observed. The second most exchanged compound was acetic acid which was captured during the entire growing season. Bi-directional exchanges of acetaldehyde and acetone were also reported. Terpene exchanges were 22 times smaller than oxygenated VOC (OVOC) exchanges. For all compounds, the exchanges were the most pronounced at the end of the growing season, i.e., under warm, dry and sunny conditions. Senescence-induced emissions were furthermore observed for methanol and acetaldehyde. For all investigated OVOCs, the exchanges very likely originated from both the soil and the plants. Despite their mixed origin, the MEGAN (Model of Emissions of Gases and Aerosols from Nature) v2.1 up-scaling model could adequately reproduce the methanol, acetaldehyde and acetone exchanges measured at this site during the mature and senescence phases of the plant, when the standard emission factor and the leaf age factor were adapted based on the measurements. In contrast, the model failed to reproduce the measured acetic acid exchanges. When the standard emission factor values currently assigned in MEGAN were applied, however, the exchanges were largely over-estimated for all compounds. Highlights: The winter wheat field exchanged mainly methanol and other OVOCs. Warm conditions favoured methanol, acetaldehyde and acetone emissions. Fitted MEGAN v2.1 succeeded in reproducing their exchange dynamics. Warm conditions favoured acetic acid uptake. Senescence-induced emissions were reported for methanol and acetaldehyde.